Efficient Photoelectrochemical Water Oxidation by Metal-Doped Bismuth Vanadate Photoanode with Iron Oxyhydroxide Electrocatalyst. (18th May 2016) - Joo, Eun Jin; Park, Gisang; Gwak, Ji Seon; Seo, Jong Hyeok; Jang, Kyu Yeon; Oh, Kyung Hee; Nam, Ki Min
Abstract : Intensive attention has been currently focused on the discovery of semiconductor and proficient cocatalysts for eventual applications to the photoelectrochemical water splitting system. A W-Mo-doped BiVO4 semiconductor was prepared by the surfactant-assisted thermal decomposition method on a fluorine-doped tin oxide conductive film. The W-Mo-doped BiVO4 films showed a porous morphology with the grain sizes of about 270 nm. Because the hole diffusion length of BiVO4 is about 100 nm, the W-Mo-doped BiVO4 film in this study is an ideal candidate for the photoelectrochemical water oxidation. Iron oxyhydroxide (FeOOH) electrocatalyst was chemically deposited on the W-Mo-doped BiVO4 to investigate the effect of the electrocatalyst on the semiconductor. The W-Mo-doped BiVO4 /FeOOH composite electrode showed enhanced activity compared to the pristine W-Mo-doped BiVO4 electrode for water oxidation reaction. The chemical deposition is a promising method for the deposition of FeOOH on semiconductor.